SEX IN RECENT GENDER POLICIES: INTERDISCIPLINARY REFLECTIONS ON THE X V. NORTH MACEDONIA CASE BEFORE THE ECTHR - Ignovska, Elena; Arsov, Todor (Serbian political thought, 2025)
This article was initially prompted by the inconsistent use of the terms sex and gender in the landmark case X v. the Former Yugoslav Republic of Macedonia (now Republic of North Macedonia) before the European Court of Human Rights (ECtHR). Although the judgment was delivered several years ago, national legal implementation remains incomplete and, to some extent, problematic. This topic remains timely more broadly, given the limited engagement of English legal discourse with the ECtHR’s evolving approach to gender recognition. The authors investigate why a seemingly straightforward legal adjustment, such as introducing a gender marker on birth certificates, has proven so contentious. Their inquiry revealed that the term gender, originally introduced to distinguish from sex, has been increasingly subsumed into the concept of sex, often being used interchangeably. The Court’s judgment reflects this conflation: at times it refers to sex, at others to gender, and frequently to both (e.g., sex/gender) without clear differentiation. This raises critical questions, foremost among them: Why was there such a concerted effort to establish gender as distinct from sex when some of the same actors now assert that the two are effectively synonymous? While the X v. North Macedonia judgment marks a significant step in affirming transgender rights, it also exposes the ECtHR’s ongoing terminological ambiguity. In the absence of clear and consistent language, and in pursuit of fulfilling human rights obligations, particularly under articles 8 and 14 of the ECtHR, a legal compromise has emerged: recognizing gender identity as a fundamental aspect of personal identity, protected under the right to respect for private life.